Characterization of several hazelnut (Corylus avellana L.) cultivars based in chemical, fatty acid and sterol composition - Amaral, Joana S. (2006)
Nineteen cultivars of hazelnuts (Corylus avellana L.) collected during the 2001 crop, from Vila Real, Portugal, were analysed for chemical composition, including moisture, total oil content, crude protein, ash, carbohydrates and nutritional value. Fat was the predominant component, ranging from 59.3 to 69.0%. Total oil was extracted and analysed for fatty acid and sterol compositions and oxidative stability. Fatty acid and sterol compositions were determined by Gas–Liquid Chromatography coupled to a Flame Ionisation Detector (GLC/FID). Monounsaturated fatty acids, particularly oleic acid, were predominant (78.7–84.6%). Total phytosterol content ranged from 133.8 to 263.0 mg/100 g of oil. Among the nine sterols identified and quantified, β-sitosterol was the major one with a mean percentage of 83.6%, while Δ5-avenasterol and campesterol were the second and the third components of the group with mean values of 6.1 and 5.8%, respectively. Since hazelnut oil can be used in olive oil adulteration, the values obtained were compared with published mean values of olive oils from different geographical origins.